Development of a Device to Measure Human Hair Luster - Tango, Yutaka; Shimmoto, Koichi (Journal of Society of Cosmetic Chemists of Japan, 1999)
Evaluating human hair luster is important to develop hair-care products. Many methods to measure human hair luster have been proposed so far. However, they have some disadvantages: some method needs to cut subject's hair and some needs a long time of period. To solve these problems, a new device to measure human hair luster is developed. This new device has some excellent features: It can measure human hair luster accurately without cutting hair. The measurement is not affected by subject's hairstyle and/or color. The device needs extremely short time of period. The relationship between sensory data of human hair luster and the measurement has highly correlative coefficient, so the measurement by this new device is effective for evaluating human hair luster.